Hubungan Tingkat Pengetahuan Tentang Vaksinasi Terhadap Kesediaan Vaksinasi Booster COVID-19 Pada Radiografer di Wilayah Jember - Pangastuti, Fadilah Tyas Widarti; Prasetyarini, Swasthi; Soesetijo, FX Ady (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Radiographers are at high risk of being infected with COVID-19 related to the most common transmission of COVID-19, so radiographers must be vaccinated. Antibody levels from primary vaccine can only last for 12 to 20 weeks, so booster vaccine is needed. Booster vaccination is one of health behaviors that divided into three domains: cognitive (knowledge), affective (attitudes), and psychomotor (actions). Based on the background above, the authors are interested in researching the relationship between knowledge level about vaccination and willingness to be vaccinated COVID-19 booster among radiographers at Jember. This type of research is a correlational analytic survey with a cross-sectional approach. Population in this research were all radiographers who are members of the Indonesian Radiographers Association (PARI) and active in Jember. The sampling method using total sampling (n=60). Data analysis in this research included editing, scoring, coding, tabulating, univariate analysis, normality test, and bivariate analysis (Rank Spearman Correlation Test) using IBM SPSS Statistics 25 software. Respondent's knowledge level about vaccination showed 46% good, 27% moderate, and 27% less. Respondent’s willingness to be vaccinated COVID-19 booster showed 47% good, 43% moderate, and 10% less. Rank Spearman Correlation Test (Spearman Rho) showed p value or Sig. (2- tailed) of 0.001 and correlation coefficient was 0.43 (+). There is a significant relationship between knowledge level and willingness to be vaccinated COVID-19 booster among radiographers at Jember with moderate correlation strength and unidirectional correlation.